2021
DOI: 10.1126/sciadv.abd2368
|View full text |Cite
|
Sign up to set email alerts
|

De novo ATP1A3 variants cause polymicrogyria

Abstract: Polymicrogyria is a common malformation of cortical development whose etiology remains elusive. We conducted whole-exome sequencing for 124 patients with polymicrogyria and identified de novo ATP1A3 variants in eight patients. Mutated ATP1A3 causes functional brain diseases, including alternating hemiplegia of childhood (AHC), rapid-onset dystonia parkinsonism (RDP), and cerebellar ataxia, areflexia, pes cavus, optic nerve atrophy, and sensorineural deafness (CAPOS). However, our patients showed no clinical fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In addition, the heterozygous deletion identified in Proband 2 also included ATP1A3, which has been associated with Mendelian disease. Although heterozygous missense and small in-frame deletion/insertion ATP1A3 variants have been associated with various ATP1A3 -related neurologic disorders inherited in an autosomal dominant pattern, including dystonia and CAPOS syndrome (cerebellar ataxia, areflexia, pes cavus, optic atrophy, sensorineural hearing loss), haploinsufficiency has not been proposed as a pathogenic mechanism of disease ( Brashear et al 1993 ; Miyatake et al 2021 ). However, a contiguous gene deletion effect of the heterozygous 583.2-kb deletion in Proband 2 cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the heterozygous deletion identified in Proband 2 also included ATP1A3, which has been associated with Mendelian disease. Although heterozygous missense and small in-frame deletion/insertion ATP1A3 variants have been associated with various ATP1A3 -related neurologic disorders inherited in an autosomal dominant pattern, including dystonia and CAPOS syndrome (cerebellar ataxia, areflexia, pes cavus, optic atrophy, sensorineural hearing loss), haploinsufficiency has not been proposed as a pathogenic mechanism of disease ( Brashear et al 1993 ; Miyatake et al 2021 ). However, a contiguous gene deletion effect of the heterozygous 583.2-kb deletion in Proband 2 cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…PMG PMG is the most common developmental malformation of the cerebral cortex, characterised by abnormal folding and laminar organisation. Recently, de novo and familial mutations in ATP1A3 were found in patients affected by a severe form of PMG characterised by epilepsy and a global developmental delay (Miyatake et al, 2021;Smith et al, 2021;Vetro et al, 2021). PMG mutations include D801N, the most common mutation in AHC (Panagiotakaki et al, 2015), and L924P, which is also observed in early infantile epileptic encephalopathy (EIEE) (Arystarkhova et al, 2019).…”
Section: Capos Syndromementioning
confidence: 99%
“…PMG mutations include D801N, the most common mutation in AHC ( Panagiotakaki et al, 2015 ), and L924P, which is also observed in early infantile epileptic encephalopathy (EIEE) ( Arystarkhova et al, 2019 ). A human ATP1A3 complementary DNA (cDNA) construct harbouring the mutation D992del, observed in two patients with severe PMG, was found to impair radial neuronal migration in the cerebral cortex of C57BL/6 mice at embryonic day (E)18.5, after being introduced into the ventricles on E14.5 by in utero electroporation ( Miyatake et al, 2021 ), suggesting that ATP1A3 D992del causes defects in cortical architecture.…”
Section: Introductionmentioning
confidence: 99%
“…So far, none of the reported ATP1A3 variants associated with polymicrogyria reported are homozygous truncating mutations but are all heterozygous variants. The recent molecular study suggested the mechanistic basis in ATP1A3-associated polymicrogyria be a dominant-negative effect rather than simple loss-of-function (Miyatake et al, 2021).…”
Section: Broadinstituteorg/)mentioning
confidence: 99%